Stakeholder perceptions of relationships and sexuality education, backlash and health services in a rural town - Heslop, Carl; Burns, Sharyn; Lobo, Roanna (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2020)
This paper examines the provision of youth targeted Relationships and Sexuality Education (RSE) and sexual health interventions in the rural Australian context by examining the perspectives and experiences of a range of community stakeholders. Sixteen participants undertook one-on-one semi structured interviews. Four key themes emerged from the data and included: ‘you’re not going to get the whole town to start thinking about adolescent sexual health’; backlash, stigma and secrecy; being consistent, credible and available; and small-town communication. This study contributes to the limited literature about RSE and sexual health provision in regional and rural Australia and provides a voice for rural stakeholders who provide RSE and sexual health interventions by default or necessity. The findings of this study have practical implications for rural settings when addressing youth sexual health needs.